Anaplasma phagocytophilum APH_1387 Is Expressed throughout Bacterial Intracellular Development and Localizes to the Pathogen-Occupied Vacuolar Membrane - Huang, Bernice (American Society for Microbiology (ASM), 2010)
Obligate vacuolar pathogens produce proteins that localize to the host cell-derived membranes of the vacuoles in which they reside, yielding unique organelles that are optimally suited for pathogen survival. Anaplasma phagocytophilum is an obligate vacuolar bacterium that infects neutrophils and causes the emerging and potentially fatal disease human granulocytic anaplasmosis. Here we identified APH_1387 as the first A. phagocytophilum-derived protein that associates with the A. phagocytophilum-occupied vacuolar membrane (AVM). APH_1387, also referred to as P100, is a 61.4-kDa acidic protein that migrates with an apparent molecular weight of 115 kDa on SDS-PAGE gels. It carries 3 tandem direct repeats that comprise 58% of the protein. Each APH_1387 repeat carries a bilobed hydrophobic alpha-helix domain, which is a structural characteristic that is consistent with the structure of chlamydia-derived proteins that traverse inclusion membranes. APH_1387 is not detectable on the surfaces of A. phagocytophilum dense core organisms bound at the HL-60 cell surface, but abundant APH_1387 is detected on the surfaces of intravacuolar reticulate cell and dense core organisms. APH_1387 accumulates on the AVM throughout infection. It associates with the AVM in human HL-60, THP-1, and HMEC-1 cells and tick ISE6 cells. APH_1387 is expressed and localizes to the AVM in neutrophils recovered from A. phagocytophilum-infected mice. This paper presents the first direct evidence that A. phagocytophilum actively modifies its host cell-derived vacuole.